Pengaruh Komitmen Terhadap Keset Pengaruh Komitmen Terhadap Kesetiaan Pasangan Di Desa Nebe: Pengaruh Komitmen Terhadap Kesetiaan Pasangan Di Desa Nebe - Angelina Br. Barus, Debi; Hans Monteiro, Yohanes; Martina Peni, Fransiska; Tela, Tekladia Dadi; Fransiska Kleden, Maria; Alexandro, Fransesco (ABIDUMASY, 2024)
The aim of this research is to find out whether commitmen influences the loyalty of married couples who are having an affair. The method used is quantitative experimental research, with a two groups research design. The population in this study was 30 husband and wife pairs, with the research sampel using purposive sampling. The research result show that there is a positive and significant influence with the test value (hypothesis) sig. (2-tailed is 0.000<0.05), meaning that commitment influences the loyalty of husband and wife couples who have an affair. So it can be concluded that commitment influences the loyalty oh husband and wife couples who have an affair.